Sistem Informasi Promosi Dan Pelayanan Administrasi Desa Berbasis Web : Sistem Informasi Promosi Dan Pelayanan Administrasi Desa Berbasis Web - Yunus Hidayat; Andilala; Guntur Alam (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2022)
Abstract— Even though they are located in an area that is not far apart, there are still communication problems between the community and the village government. This can be caused by the limited information media that can be used by the village government, which only uses the village bulletin board, with the village website, the village government can provide information directly to the community and the community can directly know and interact with the village government without any time limit. The purpose of this research is to create a website that can be used as a medium for village promotion and village administration management. System development method using waterfall, system design using system modeling based on Data Flow Diagrams (DFD) and system testing using whitebox testing. The test results of the website-based promotion information system and village administration services are as expected based on 3 variables, namely: The assessment of the display variable is in the